A composite binder for sulfide solid-state battery and its preparation method and application
By using a combination technology of a binder with polar functional groups and a low-polar/non-polar adhesive in a sulfide-based all-solid-state battery, the problem that binders in the prior art are difficult to take into account the mechanical properties, flexibility and ionic conductivity of the sulfide solid electrolyte membrane, and better battery performance is achieved.
Patent Information
- Application Number
- CN202411942603.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to select a suitable binder when preparing a sulfide-based all-solid state battery, so as not to reduce the ionic conductivity of the sulfide solid electrolyte, but also to take into account the mechanical properties and flexibility of the film.
The adhesive A with polar functional groups is combined with the low-polar/non-polar adhesive B to regulate the adhesion and flexibility of the composite adhesive, so that it has good compatibility with the sulfide solid electrolyte.
The sulfide solid electrolyte membrane has achieved good mechanical properties and flexibility without affecting its ionic conductivity.
Smart Images

Figure BDA0005214818030000111
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state batteries and relates to a composite binder for sulfide solid-state batteries and a preparation method and application thereof. Background Art
[0002] Among various types of all-solid-state batteries, sulfide-based all-solid-state batteries have become the most promising choice for electric vehicles due to their high ionic conductivity. However, due to the sensitivity of sulfide solid electrolytes to air / moisture and poor mechanical properties, it is challenging to manufacture sulfide-based all-solid-state batteries using traditional wet processes, especially the high reactivity with conventional polar solvents, and the selection of suitable solvents and binders becomes the key. Therefore, the industry focuses on the preparation of sulfide solid electrolytes using non-polar solvents or low-polar solvents. Traditional polar binders are difficult to dissolve in non-polar or low-polar solvents. Considering the compatibility of sulfide solid electrolytes (SE) with solvents, most of the industry uses low-polarity or non-polar binders in combination with solvents. However, low-polarity or non-polar binders are difficult to effectively adhere to SE particles, resulting in poor mechanical properties of the prepared sulfide solid electrolyte membrane. The polar functional groups contained in the polar binder will react with the sulfide solid electrolyte to reduce its ionic conductivity. In addition, the prepared sulfide solid electrolyte membrane must also have a certain flexibility to adapt to the volume expansion of particles during the charging and discharging process of sulfide-based all-solid-state batteries.
[0003] Therefore, how to select a suitable binder to prepare the sulfide solid electrolyte, that is, not reducing the ionic conductivity of the sulfide solid electrolyte while taking into account the mechanical properties and flexibility of the sulfide solid electrolyte membrane, is a problem that needs to be solved. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a composite binder for sulfide solid-state batteries, a preparation method and an application thereof. By combining a binder with a polar functional group with a low-polarity / non-polar binder, the prepared composite binder has good compatibility with the sulfide solid electrolyte, that is, it does not affect the ionic conductivity of the sulfide solid electrolyte, and at the same time, the sulfide solid electrolyte membrane has good mechanical properties and flexibility.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a composite adhesive, comprising an adhesive A, an adhesive B and a solvent, wherein the mass ratio of the adhesive A to the adhesive B is (1-10):(5-1), and the mass ratio of the total mass of the adhesive A and the adhesive B to the solvent is 1:(10-100);
[0007] The adhesive A includes any one of an acrylate adhesive, an amide adhesive, a polyurethane adhesive, a polyvinyl alcohol adhesive or a polyvinylidene fluoride adhesive, or a combination of at least two thereof;
[0008] The binder B includes any one of polyisobutylene, nitrile rubber or styrene butadiene rubber or a combination of at least two thereof;
[0009] The solvent includes any one of xylene, toluene, acetonitrile or anisole, or a combination of at least two of them.
[0010] As a preferred embodiment of the present invention, the acrylic ester adhesive includes acrylic ester monomers and / or acrylic ester polymers.
[0011] As a preferred embodiment of the present invention, the amide binder includes amide monomers and / or amide polymers.
[0012] As a preferred embodiment of the present invention, the acrylic acid ester monomer includes any one of methyl acrylate, ethyl acrylate, glycidyl methacrylate or methyl methacrylate, or a combination of at least two thereof.
[0013] As a preferred embodiment of the present invention, the amide monomer includes any one of acrylamide, caprolactam or formamide, or a combination of at least two of them.
[0014] As a preferred embodiment of the present invention, the acrylic ester polymer includes any one of polymethyl acrylate, polyethyl acrylate, polyglycidyl methacrylate or polymethyl methacrylate, or a combination of at least two thereof.
[0015] As a preferred embodiment of the present invention, the amide polymer includes any one of polyamide, polyimide or polyacrylamide, or a combination of at least two of them.
[0016] As a preferred embodiment of the present invention, the polyurethane adhesive includes acrylonitrile resin and / or polyurethane.
[0017] As a preferred embodiment of the present invention, the polyvinyl alcohol-based binder includes polyvinyl alcohol and / or polyvinyl butyral.
[0018] As a preferred embodiment of the present invention, the polyvinylidene fluoride binder is polyvinylidene fluoride and / or poly(vinylidene fluoride-co-hexafluoropropylene).
[0019] In a second aspect, the present invention provides a method for preparing the aforementioned composite binder, the preparation method comprising:
[0020] Binder B is added to a mixed solution of binder A and a solvent, and the mixture is mixed to obtain a composite binder.
[0021] As a preferred embodiment of the present invention, the method for preparing the mixed solution of the binder A and the solvent comprises: mixing the binder A and the solvent at a rotation speed of 100 r / min-8000 r / min.
[0022] As a preferred embodiment of the present invention, the mixing is carried out at a rotation speed of 100 r / min-8000 r / min.
[0023] In a third aspect, the present invention provides a sulfide solid electrolyte membrane, wherein the sulfide solid electrolyte membrane is prepared using the aforementioned composite binder.
[0024] In a fourth aspect, the present invention provides a sulfide solid-state battery, wherein the sulfide solid-state battery comprises the aforementioned sulfide solid-state electrolyte membrane.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention adopts a combination of a binder with a polar functional group and a low-polarity / non-polar binder to adjust the adhesion and flexibility of the composite binder, thereby making the prepared composite binder have good compatibility with the sulfide solid electrolyte, that is, it does not affect the ionic conductivity of the sulfide solid electrolyte, and at the same time makes the sulfide solid electrolyte membrane have good mechanical properties and flexibility. DETAILED DESCRIPTION
[0027] In order to better illustrate the present invention and facilitate understanding of the technical solution of the present invention, the present invention is further described in detail below. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0028] In a first aspect, a specific embodiment of the present invention provides a composite adhesive, wherein the composite adhesive comprises an adhesive A, an adhesive B and a solvent, wherein the mass ratio of the adhesive A to the adhesive B is (1-10):(5-1), for example, 1:(5-1), 2:(5-1), 4:(5-1), 6:(5-1), 8:(5-1), 10:(5-1), (1-10):1, (1-10):2, (1-10):3, (1-10) :4 or (1-10):5, etc., but are not limited to the listed values, and other values not listed within the numerical range are equally applicable; the mass ratio of the total mass of binder A and binder B to the solvent is 1:(10-100), for example 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90 or 1:100, etc., but are not limited to the listed values, and other values not listed within the numerical range are equally applicable;
[0029] The adhesive A includes any one of an acrylic adhesive, an amide (PA) adhesive, a polyurethane (PU) adhesive, a polyvinyl alcohol (PVA) adhesive, or a polyvinylidene fluoride (PVDF) adhesive, or a combination of at least two thereof;
[0030] The binder B includes any one of polyisobutylene, nitrile rubber or styrene butadiene rubber or a combination of at least two thereof;
[0031] The solvent includes any one of xylene, toluene, acetonitrile or anisole, or a combination of at least two of them.
[0032] In this field, polarity depends on the overlap of positive and negative charge centers within a molecule. The higher the overlap, the lower the polarity, or the more symmetrical the molecular structure, the lower the polarity.
[0033] The present invention selects a binder A with polar functional groups and a low polarity / non-polar binder B, and utilizes the strong attraction of the polar functional groups to cause the electron cloud and the nucleus of the low polarity / non-polar molecule to be relatively displaced, and the center of gravity of the positive and negative charges changes from overlapping to non-overlapping, resulting in the deformation of the molecule, thereby generating an induced dipole. As a result, additional attraction occurs between the low polarity / non-polar molecules, increasing the strong attraction and interaction of the composite binder. In addition, the side reactions derived from the low polarity or non-polar binder and the sulfide solid electrolyte are relatively few, and the molecules have a certain flexibility. Thus, the prepared composite binder has good compatibility with the sulfide solid electrolyte, that is, it does not affect the ionic conductivity of the sulfide solid electrolysis, and at the same time, the sulfide solid electrolyte membrane has good mechanical properties and flexibility.
[0034] In the present invention, the amount of binder A needs to be controlled within a certain range. If the amount of binder A is too much, more side reactions will be derived from the sulfide solid electrolyte, reducing the ionic conductivity of the sulfide solid electrolyte; if the amount of binder A is too little, the bonding force between the solid particles in the sulfide solid battery will be reduced, and the prepared diaphragm will be prone to cracks, affecting its electrochemical properties.
[0035] As a preferred embodiment of the present invention, the acrylic ester adhesive comprises acrylic ester monomers and / or acrylic ester polymers, wherein the acrylic ester polymer is a polymer formed by polymerizing acrylic ester monomers.
[0036] As a preferred embodiment of the present invention, the amide binder includes amide monomers and / or amide polymers.
[0037] As a preferred embodiment of the present invention, the acrylic acid ester monomer includes any one of methyl acrylate, ethyl acrylate, glycidyl methacrylate or methyl methacrylate, or a combination of at least two thereof.
[0038] As a preferred embodiment of the present invention, the amide monomer includes any one of acrylamide, caprolactam or formamide, or a combination of at least two of them.
[0039] As a preferred embodiment of the present invention, the acrylic ester polymer includes any one of polymethyl acrylate, polyethyl acrylate, polyglycidyl methacrylate or polymethyl methacrylate, or a combination of at least two thereof.
[0040] As a preferred embodiment of the present invention, the amide polymer includes any one of polyamide, polyimide or polyacrylamide, or a combination of at least two of them.
[0041] As a preferred embodiment of the present invention, the polyurethane adhesive includes acrylonitrile resin and / or polyurethane.
[0042] As a preferred embodiment of the present invention, the polyvinyl alcohol-based binder includes polyvinyl alcohol and / or polyvinyl butyral.
[0043] As a preferred embodiment of the present invention, the polyvinylidene fluoride binder includes polyvinylidene fluoride and / or poly(vinylidene fluoride-co-hexafluoropropylene).
[0044] In a second aspect, the specific implementation of the present invention provides a method for preparing the aforementioned composite binder, the preparation method comprising:
[0045] Binder B is added to a mixed solution of binder A and a solvent, and the mixture is mixed to obtain a composite binder.
[0046] As a preferred embodiment of the present invention, the preparation method of the mixed solution of the binder A and the solvent comprises: mixing the binder A and the solvent at a rotation speed of 100r / min-8000r / min, wherein the rotation speed may be 100r / min, 300r / min, 500r / min, 800r / min, 1000r / min, 1500r / min, 2000r / min, 2500r / min, 3000r / min, 3500r / min, 4000r / min, 4500r / min, 5000r / min, 5500r / min, 6000r / min, 6500r / min, 7000r / min, 7500r / min or 8000r / min, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0047] As a preferred embodiment of the present invention, the mixing is carried out at a rotation speed of 100r / min-8000r / min, wherein the rotation speed may be 100r / min, 300r / min, 500r / min, 800r / min, 1000r / min, 1500r / min, 2000r / min, 2500r / min, 3000r / min, 3500r / min, 4000r / min, 4500r / min, 5000r / min, 5500r / min, 6000r / min, 6500r / min, 7000r / min, 7500r / min or 8000r / min, etc., but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0048] In a third aspect, a specific embodiment of the present invention provides a sulfide solid electrolyte membrane, wherein the sulfide solid electrolyte membrane is prepared by using the aforementioned composite binder.
[0049] Specifically, the sulfide solid electrolyte membrane is prepared by the following method: a sulfide solid electrolyte (Li 5.5 PS 4.5 Cl 1.5 ), add the composite binder into the ball mill at a mass ratio of 98:2, then add low polarity / non-polarity solvent, adjust the slurry solid content to 40wt%-60wt%, and then place it in a planetary ball mill to disperse it evenly at a speed of 250r / min. Use a scraper coater to coat the dispersed slurry on the current collector or positive and negative electrodes at a speed of 1cm / s with a thickness of 80μm.
[0050] In a fourth aspect, a specific embodiment of the present invention provides a sulfide solid-state battery, wherein the sulfide solid-state battery comprises the aforementioned sulfide solid-state electrolyte membrane.
[0051] The following are typical but non-limiting embodiments of the present invention:
[0052] Embodiment 1:
[0053] This embodiment provides a composite adhesive, which includes adhesive A, adhesive B and a solvent, wherein adhesive A is methyl acrylate, adhesive B is polyisobutylene, and the solvent is xylene, and the mass ratio of the three is 1:1:40. The preparation method of the composite adhesive includes:
[0054] Methyl acrylate was added to xylene, and the mixture was mixed at a speed of 200 r / min until the mixture was uniformly dispersed. Polyisobutylene was then added, and the mixture was mixed at a speed of 200 r / min until the mixture was uniformly dispersed to obtain a composite adhesive.
[0055] Embodiment 2:
[0056] This embodiment provides a composite adhesive, which includes adhesive A, adhesive B and a solvent, wherein adhesive A is ethyl acrylate, adhesive B is nitrile rubber, and the solvent is toluene, and the mass ratio of the three is 1:2:60.
[0057] The preparation method of the composite binder comprises:
[0058] Ethyl acrylate was added to toluene, and the mixture was mixed at a speed of 500 r / min until the mixture was uniformly dispersed. Then, nitrile rubber was added, and the mixture was mixed at a speed of 700 r / min until the mixture was uniformly dispersed to obtain a composite adhesive.
[0059] Embodiment 3:
[0060] This embodiment provides a composite adhesive, which includes adhesive A, adhesive B and a solvent, wherein adhesive A is glycidyl methacrylate, adhesive B is styrene-butadiene rubber, and the solvent is acetonitrile, and the mass ratio of the three is 1:2:42.
[0061] The preparation method of the composite binder comprises:
[0062] Glycidyl methacrylate was added to acetonitrile, and the mixture was mixed at a speed of 3000 r / min until the mixture was uniformly dispersed. Then, styrene-butadiene rubber was added, and the mixture was mixed at a speed of 3000 r / min until the mixture was uniformly dispersed to obtain a composite adhesive.
[0063] Embodiment 4:
[0064] This embodiment provides a composite adhesive, which includes an adhesive A, an adhesive B and a solvent, wherein the adhesive A is methyl methacrylate, the adhesive B is nitrile rubber, and the solvent is anisole, and the mass ratio of the three is 1:1:20.
[0065] The preparation method of the composite binder comprises:
[0066] Methyl methacrylate was added to anisole, and the mixture was mixed at a speed of 5000 r / min until the mixture was uniformly dispersed. Then, nitrile rubber was added, and the mixture was mixed at a speed of 5000 r / min until the mixture was uniformly dispersed to obtain a composite adhesive.
[0067] Embodiment 5:
[0068] This embodiment provides a composite adhesive, which includes an adhesive A, an adhesive B and a solvent, wherein the adhesive A is polymethyl acrylate, the adhesive B is nitrile rubber, and the solvent is anisole, and the mass ratio of the three is 1:1:20.
[0069] The preparation method of the composite binder comprises:
[0070] Polymethyl acrylate was added to anisole, and the mixture was mixed at a speed of 5000 r / min until the mixture was uniformly dispersed. Then, nitrile rubber was added, and the mixture was mixed at a speed of 5000 r / min until the mixture was uniformly dispersed to obtain a composite adhesive.
[0071] Embodiment 6:
[0072] This embodiment provides a composite adhesive, which includes an adhesive A, an adhesive B and a solvent, wherein the adhesive A is poly(ethylene-co-glycidyl methacrylate), the adhesive B is polyisobutylene, and the solvent is xylene, and the mass ratio of the three is 1:1:40.
[0073] Embodiment 7:
[0074] This embodiment provides a composite adhesive, which includes an adhesive A, an adhesive B and a solvent, wherein the adhesive A is polyamide, the adhesive B is polyisobutylene, and the solvent is xylene, and the mass ratio of the three is 1:1:40. The preparation method of the composite adhesive includes:
[0075] Methyl acrylate was added to xylene, and the mixture was mixed at a speed of 500 r / min until the mixture was uniformly dispersed. Polyisobutylene was then added, and the mixture was mixed at a speed of 200 r / min until the mixture was uniformly dispersed to obtain a composite adhesive.
[0076] Embodiment 8:
[0077] This embodiment provides a composite adhesive, which includes an adhesive A, an adhesive B and a solvent, wherein the adhesive A is polyurethane, the adhesive B is nitrile rubber, and the solvent is xylene, and the mass ratio of the three is 1:1:40. The preparation method of the composite adhesive includes:
[0078] Methyl acrylate was added to xylene, and the mixture was mixed at a speed of 800 r / min until the mixture was uniformly dispersed. Polyisobutylene was then added, and the mixture was mixed at a speed of 500 r / min until the mixture was uniformly dispersed to obtain a composite adhesive.
[0079] Embodiment 9:
[0080] This embodiment provides a composite adhesive, which includes an adhesive A, an adhesive B and a solvent, wherein the adhesive A is polyvinyl alcohol, the adhesive B is polyisobutylene, and the solvent is xylene, and the mass ratio of the three is 1:1:40. The preparation method of the composite adhesive includes:
[0081] Methyl acrylate was added to xylene, and the mixture was mixed at a speed of 500 r / min until the mixture was uniformly dispersed. Polyisobutylene was then added, and the mixture was mixed at a speed of 800 r / min until the mixture was uniformly dispersed to obtain a composite adhesive.
[0082] Embodiment 10:
[0083] This embodiment provides a composite adhesive, which includes an adhesive A, an adhesive B and a solvent, wherein the adhesive A is polyvinylidene fluoride, the adhesive B is polyisobutylene, and the solvent is xylene, and the mass ratio of the three is 1:1:40. The preparation method of the composite adhesive includes:
[0084] Methyl acrylate was added to xylene, and the mixture was mixed at a speed of 800 r / min until the mixture was uniformly dispersed. Polyisobutylene was then added, and the mixture was mixed at a speed of 200 r / min until the mixture was uniformly dispersed to obtain a composite adhesive.
[0085] Comparative Example 1:
[0086] This comparative example provides a composite adhesive, which includes polylactic acid, polyisobutylene and solvent xylene, and the mass ratio of the three is the same as that of Example 1.
[0087] The preparation method of the composite binder is the same as that of Example 1.
[0088] Comparative Example 2:
[0089] This comparative example provides a methyl acrylate adhesive.
[0090] Comparative Example 3:
[0091] This comparative example provides a polyisobutylene adhesive.
[0092] Comparative Example 4:
[0093] This comparative example provides a nitrile rubber adhesive.
[0094] Comparative Example 5:
[0095] This comparative example provides a composite adhesive, which includes poly(ethylene-co-methyl acrylate-co-glycidyl methacrylate), polyisobutylene and solvent xylene, and the mass ratio of the three is 1:10:120.
[0096] Comparative Example 6:
[0097] This comparative example provides a composite adhesive, the composition and preparation method of which are the same as those of Example 1, except that the mass ratio of methyl acrylate to polyisobutylene is 1:20.
[0098] Comparative Example 7:
[0099] This comparative example provides a composite adhesive, the composition and preparation method of which are the same as those of Example 1, except that the mass ratio of methyl acrylate to polyisobutylene is 20:1.
[0100] The sulfide solid electrolyte membrane was prepared by using the binder in Examples 1-10 and Comparative Examples 1-7, and the preparation method thereof is as follows:
[0101] The sulfide solid electrolyte (Li 5.5 PS 4.5 Cl 1.5 ), the binder is added to the ball mill at a mass ratio of 98:2, and then xylene solvent is added to adjust the slurry solid content to 45%, and then placed in a planetary ball mill to disperse evenly at a speed of 250r / min. The dispersed slurry is coated on the current collector with a scraper coater at a speed of 1cm / s at a thickness of 80μm.
[0102] The performance test of the sulfide solid electrolyte membrane prepared by the binder in Examples 1-10 and Comparative Examples 1-7 includes: measuring the ionic conductivity of the prepared sulfide solid electrolyte membrane by AC impedance spectroscopy according to the formula σ=L / (R×S) (L is the thickness, S is the effective area of the electrode). The mechanical properties of the composite binder are judged according to the peel strength of the sulfide solid electrolyte membrane. The sulfide solid electrolyte membrane is subjected to a bending test by a pole piece flexibility tester.
[0103] The test results are shown in Table 1.
[0104] Table 1: Performance test table of sulfide solid electrolyte membranes prepared by binders in Examples 1-10 and Comparative Examples 1-7
[0105]
[0106] As can be seen from Table 1, the increase in the proportion of binder type A will slightly reduce the ionic conductivity of the sulfide solid electrolyte membrane, but will increase its peel strength and reduce its flexibility. The increase in the proportion of binder type B has little effect on the ionic conductivity of the sulfide solid electrolyte membrane, but will reduce its peel strength and improve its toughness to a certain extent. A single binder type A or type B cannot take into account the ionic conductivity, mechanical properties and flexibility of the sulfide solid electrolyte membrane. If the ratio of binders type A and type B is not in an appropriate range, it is difficult for the prepared composite binder to exert the advantages of these two types of binders.
[0107] The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A composite adhesive, characterized in that: The composite adhesive comprises an adhesive A, an adhesive B and a solvent, wherein the mass ratio of the adhesive A to the adhesive B is (1-10):(5-1), and the mass ratio of the total mass of the adhesive A and the adhesive B to the solvent is 1:(10-100); The adhesive A includes any one of an acrylate adhesive, an amide adhesive, a polyurethane adhesive, a polyvinyl alcohol adhesive or a polyvinylidene fluoride adhesive, or a combination of at least two thereof; The binder B includes any one of polyisobutylene, nitrile rubber or styrene butadiene rubber or a combination of at least two thereof; The solvent includes any one of xylene, toluene, acetonitrile or anisole, or a combination of at least two of them.
2. The composite adhesive according to claim 1, characterized in that: The acrylic ester adhesive comprises acrylic ester monomers and / or acrylic ester polymers; Preferably, the amide binder includes amide monomers and / or amide polymers.
3. The composite adhesive according to claim 2, characterized in that: The acrylic acid ester monomer includes any one or a combination of at least two of methyl acrylate, ethyl acrylate, glycidyl methacrylate or methyl methacrylate; Preferably, the amide monomer includes any one of acrylamide, caprolactam or formamide, or a combination of at least two of them.
4. The composite adhesive according to claim 2, characterized in that: The acrylic polymer includes any one of polymethyl acrylate, polyethyl acrylate, polyglycidyl methacrylate or polymethyl methacrylate, or a combination of at least two thereof; Preferably, the amide polymer includes any one of polyamide, polyimide or polyacrylamide, or a combination of at least two of them.
5. The composite adhesive according to claim 1, characterized in that: The polyurethane binder includes acrylonitrile resin and / or polyurethane; Preferably, the polyvinyl alcohol-based binder includes polyvinyl alcohol and / or polyvinyl butyral; Preferably, the polyvinylidene fluoride-based binder includes polyvinylidene fluoride and / or poly(vinylidene fluoride-co-hexafluoropropylene).
6. A method for preparing the composite adhesive according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Binder B is added to a mixed solution of binder A and a solvent, and the mixture is mixed to obtain a composite binder.
7. The preparation method according to claim 6, characterized in that: The method for preparing the mixed solution of the binder A and the solvent comprises: mixing the binder A and the solvent at a rotation speed of 100 r / min-8000 r / min.
8. The preparation method according to claim 6, characterized in that: The mixing is performed at a rotation speed of 100 r / min-8000 r / min.
9. A sulfide solid electrolyte membrane, characterized in that: The sulfide solid electrolyte membrane is prepared by using the composite binder as described in any one of claims 1 to 5.
10. A sulfide solid-state battery, characterized in that: The sulfide solid-state battery comprises the sulfide solid-state electrolyte membrane as claimed in claim 9.
Citation Information
Cited By
Preparation method and application of single ion conductor composite binder
CN120025762A
Solid-state battery binder, preparation method and application thereof, composite electrolyte membrane and solid-state battery composite positive electrode
CN120290124A
Single-ion conductor polymer, ternary composite binder solution, high-solid-content sulfide electrolyte slurry and wet film forming method and application of high-solid-content sulfide electrolyte slurry
CN121021736A
Binder for sulfide solid electrolyte and application thereof
CN121718282A
Modified PVDF (Polyvinylidene Fluoride) binder for sulfide all-solid-state battery as well as preparation method and application of modified PVDF binder
CN121780077A